Innovative multi-protectoral approach increases survival rate after vitrification of ovarian tissue and isolated follicles with improved results in comparison with conventional method - Dmitry Nikiforov; Valentina Russo; Delia Nardinocchi; Nicola Bernabò; Mauro Mattioli; Barbara Barboni (BMC, 2018)
Abstract Background In recent years, autotransplantation of cryopreserved ovarian tissue became a promising approach to preserve female fertility. The slow freezing is the most effective technique which resulted in greater live birth incidence so far. Despite that, interest to vitrification of the ovarian tissue is swiftly growing, thereby undermining the necessity for further improvements in the technique. In present study, we evaluated possibilities to increase follicle survival rates adopting innovative multi-protectoral vitrification protocols, applied to the slivers of ovarian cortex or isolated early-antral follicles, frozen individually. These experimental protocols have been compared with with validated vitrification and slow freezing ones, clinically used for female fertility preservation. Results The results showed that third tested variation of experimental vitrification protocol, with four cryoprotectants in relatively low concentrations and applied to pieces of ovarian tissue at 0 °C during equilibration, increased survival rate of ovine ovarian tissue and improved results in comparison with conventional vitrification method. This variation of experimental protocol showed significant increase in percentage of follicles with good morphology (69,3%) in comparison with only commercially available vitrification protocol for ovarian tissue (62,1%). Morphology results were confirmed by TUNEL assay. Analysis of estradiol and progesterone production by cultured individual follicles after freezing/thawing revealed that steroids secretion remained significantly higher after multi-protectoral vitrification and slow freezing protocol, when follicles after standard vitrification protocol demonstrated decline in steroidogenic activity. Conclusions The multi-protectoral approach represents a workable solution to improve vitrification outcome on ovarian tissue and isolated follicles. The reduction of individual cryoprotectants concentrations, while maintaining their sufficient cumulative level in the final freezing solution, helps to increase efficiency of the procedure. Moreover, equilibration with lower temperatures helped to decrease even further the toxic effects of cryoprotectants and preserve original quality of ovarian tissue. Therefore, multi-protectoral vitrification can be suggested as an improved method for the clinical cryopreservation of ovarian tissue.